Sex differences in the relationship between individual systemic markers of inflammation and pain in knee osteoarthritis. Issue 1 (November 2019) - Perruccio, Anthony V.; Badley, Elizabeth M.; Power, J. Denise; Canizares, Mayilee; Kapoor, Mohit; Rockel, Jason; Chandran, Vinod; Gandhi, Rajiv; Mahomed, Nizar M.; Davey, J. Roderick; Syed, Khalid; Veillette, Christian; et al.
Summary: Objective: There are suggestions that the relationship between inflammation and pain in osteoarthritis (OA) may differ by sex, yet studies have been limited. We investigated whether the relationship between knee-specific OA pain and systemic inflammatory markers differs by sex. Design: 196 patients scheduled for knee arthroplasty for OA were included. Questionnaires were completed and blood samples drawn pre-surgery. Questionnaire data: knee pain (WOMAC), sex, age, height, weight, comorbidities, depressive symptoms, and symptomatic joint count. Systemic inflammatory markers (cytokines IL-6, IL-8, IL-10, IL-1β and TNF-α) were measured by multiplex ELISA. A series of regression models with interaction terms between sex and ln-transformed inflammatory markers were estimated with pain score as the outcome. The adjusted relationship between pain and inflammatory markers, by sex, were presented graphically. Results: Mean age was 64 years (range 43–89); females comprised 58.7% of the sample. In adjusted analyses, similar relationships between knee pain and lnIL-10 (negative: β ​= ​−1.28, 95%CI (−1.97, −0.58)) and lnTNF-α (positive: β ​= ​0.92, 95%CI (0.11, 1.76)) were found for females and males. In contrast, relationships between knee pain and lnIL-1β, lnIL-6 and lnIL-8 differed in direction for females and males. Specifically, for lnIL-1β and lnIL-8 they were positive for males, negative for females. The opposite was found with lnIL-6, negative for males, positive for females. Conclusion: These findings provide some evidence of sex-specific relationships between individual inflammatory markers and knee OA pain. They expose a need for further exploration of sex-differences in this context, with potential future implications for treatment or drug development in OA.